Emotional Excess on the Shakespearean Stage Passion's Slaves - Escolme, Bridget (Bloomsbury Academic, 2013)
Emotional Excess on the Shakespearean Stage demonstrates the links made between excess of emotion and madness in the early modern period. It argues that the ways in which today's popular and theatrical cultures judge how much is too much can distort our understanding of early modern drama and theatre. It argues that permitting the excesses of the early modern drama onto the contemporary stage might free actors and audiences alike from assumptions that in order to engage with the drama of the past, its characters must be just like us. The book deals with characters in the plays of Shakespeare and his contemporaries who are sad for too long, or angry to the point of irrationality; people who laugh when they shouldn't or make their audiences do so; people whose selfhood has broken down into an excess of fragmentary extremes and who are labelled mad.